2018
DOI: 10.1016/j.ijthermalsci.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation spatial distribution of droplets and the percentage of surface coverage during dropwise condensation

Abstract: The aim of this research is to develop an algorithm to simulate droplets nucleation and growth during dropwise condensation in order to study the droplets spatial distribution. The proposed algorithm starts with droplets distributed based on the Poisson point process and investigates the spatial distribution of droplets using Ripley's L function method. Also, the effects of substrate temperature (T w) and initial density (N D) on the percentage of area occupied by droplets (φ) are studied. Good agreement betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Mei et al used a computer simulation to obtain the drop distribution also for a contact angle of 90°, but their results were intended for larger drop sizes where the distribution function was already well established . Barati et al used a numerical simulation of dropwise condensation to investigate condensation as a function of time for drops with a contact angle of 88°, though they did not report steady state drop distribution data . Meng et al demonstrated how a computer simulation could incorporate the possibility of coalescence-induced jumping but did not use their model to obtain an expression for the drop-size distribution and focused on predicting heat transfer for drops with a single contact angle (140°) and maximum drop size (30 μm) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mei et al used a computer simulation to obtain the drop distribution also for a contact angle of 90°, but their results were intended for larger drop sizes where the distribution function was already well established . Barati et al used a numerical simulation of dropwise condensation to investigate condensation as a function of time for drops with a contact angle of 88°, though they did not report steady state drop distribution data . Meng et al demonstrated how a computer simulation could incorporate the possibility of coalescence-induced jumping but did not use their model to obtain an expression for the drop-size distribution and focused on predicting heat transfer for drops with a single contact angle (140°) and maximum drop size (30 μm) .…”
Section: Introductionmentioning
confidence: 99%
“…The present work reports a computational approach to obtain the steady state drop-size distribution and associated time-averaged heat transfer rates for dropwise condensation over a range of contact angles from 90 to 180°. Condensation is simulated in a Lagrangian approach, similar in form to previous computational approaches, allowing for coalescence at naturally occurring drop sizes. , Unlike previous computational simulations, the present work considers how the departure of drops both by jumping and gravity-induced sweeping influences the steady state drop-size distribution and associated time-averaged heat transfer rates. The present work spans also a larger range of physical conditions than previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…As it was explained in our former works [25,26], the process of dropwise condensation consists of four main steps: nucleation of initial droplets, growth rate due to adsorption, growth rate due to coalescence followed by nucleation of new small droplets, and sliding of the very big droplets from the surface. There are two kinds of growth procedures for each droplet regardless of its size and shape:…”
Section: Growth Rate Of Ellipsoidal Dropletsmentioning
confidence: 99%
“…where k represents each generation of droplets, ∆t is the time step, and , and C 3 = θ 4KwSinθ [25,27]. Miljkovic et al [4,28,29] have done considerable efforts to calculate the growth rate of jumping and non-jumping cassie-baxter and Wenzel droplets on the super-hydrophobic pillared substrates.…”
Section: Adsorptionmentioning
confidence: 99%
“…For faster atmospheric water capture (and higher heat transfer), water should condense in droplet form (dropwise condensation, contact angle > 0°), rather than filmwise condensation, [ 22–27 ] as droplets drastically decrease the thermal resistance of the process. Droplets should roll‐off the surface at small volumes, allowing the free surface area to nucleate new droplets at a higher rate.…”
Section: Introductionmentioning
confidence: 99%